Keluarga Tradisional dan Modern (Dual Career), Tipologi dan Permasalahannya - David Ilham Yusuf (Fakultas Dakwah IAIN Jember, 2019)
This study aimed at understanding the kinds of issues occur in families which apply traditional pattern and modern pattern or known as dual-career family (both husband and wife are employed). This descriptive qualitative study had eight (8) families as the respondents. Four families were considered as traditional families, while the other four applied modern pattern or known as dual-career families. The data were obtained from interviews and observations which were then triangulated to validate the data. The current study revealed the following issues as the results found in traditional family: First, husbands expected wives to have a job which were followed with the use of harsh words towards their wives. The second issue, husbands were negligent towards child care and education as they considered children as wives’ responsibility. Third, extramarital affair caused by unsatisfied spouses and lack of affection from their respective partners. As for the issues emerged in a modern or dual-career family are stated as follows: First, the dual-role of a wife which later sparked family conflicts. Second, a very limited family time, and the third was the lack of affection from their respective spouses.